Descentralización en Ecuador ¿Un proceso inconcluso? - Tello Toral , Karina Patricia (2019)
This research analyzes the process of decentralization in the Republic of Ecuador during the 2008 – 2018 period through the structuring of two paradigms: first, the current administrative political division, and second, the process of competences in each one of the levels of government. Regarding the methodology in this proposal, are used the systematic and analytical methods applied to the field of Social Sciences. The investigation concludes stating that the process of decentralization from the Political Constitution of 2008 is an unfinished avatar.